Distribution of nutrients in Camellia oleifera Abel. and their correlation with soil nutrients over the period of fruit maturation - Luo, Jia; Zhou, Xiaoling; Tian, Yuxin; Chen, Yongzhong; Chen, Longshen (Bangladesh Journal of Botany, 2020)
In order to provide the scientific basis for Camellia oleifera nutrient diagnosis and fertilizer formulation, the correlation between soil nutrients and nutrient elements in different organs of Camellia oleifera was studied in ten-year-old Camellia oleifera in Changning city. The results showed that among the nutrient elements, the content of N and P were the highest and lowest in various organs, respectively. Correspondingly, the highest content of macro-element in the soil was Ca. Besides, there were diverse relations among nutrients in soil and those in different organs of Camellia oleifera. Soil nutrients were most closely associated with that of stem, so was soil N, Zn, Mn, Pb and K with the plant nutrients. In addition, soil exchangeable Mn content was positively correlated with nutrients of different organs. Moreover, soil N showed highly significant correlation with N content in stem while soil Cd content was negatively correlated with Cd content of all organs. Thus, there prevails a complex interaction of nutrient elements in the soil and exists a synergy or/and antagonism effect among of elements in plants. Consequently, the understanding of effect of interaction between different elements might provide better idea for achieving the precise fertilization, which could further reduce costs and increase production.